INFUSING ISLAMIC VALUES INTO ENGLISH LEARNING: CREATING AN INTERACTIVE E-MODULE FOR ISLAMIC SECONDARY SCHOOL STUDENTS: English - Risky Amelia; Syahid, Abdul; Widiastuty, Hesty (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2025)
English language learning in Islamic schools often struggles to provide materials aligned with cultural and religious values. This study aimed to develop an interactive English e-module that integrates Islamic values to support the language skills of eighth-grade students in Islamic secondary school. The research employed a Research and Development (R&D) approach and applied the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model proposed by Branch (2009). Data were collected through interviews, documentation, questionnaires, and User Experience Questionnaires (UEQ). Results indicated that the e-module was deemed feasible by both material and media experts. During implementation, evaluations from 41 students revealed a positive assessment across all aspects including attractiveness, perspective, efficiency, dependability, stimulation, and novelty. This e-module combined multimedia elements and interactive activities to support language skills (listening, reading, speaking, writing) while instilling Islamic values. It was hoped that this interactive e-module would be an effective supplementary learning tool to improve students' English language skills while strengthening their understanding of Islamic values, both at school and at home. This study offered a structured approach to integrating religious values into language learning through digital tools, providing insights for future curriculum development.